Asymmetric rhodium catalysed additions to activated imines : new approaches to α-chiral amines - Crampton, Rosemary Helen (2012)
This Thesis details the development of a series of rhodium catalysed asymmetric additions to activated aldimines to give enantioenriched protected secondary amines. A particular focus has been the choice of activating group to allow deprotection of the protected amines under mild conditions, which would tolerate a wide substrate scope. Initially methyl addition to give enantioenriched arylethanamines was studied, using diphenylphosphinoyl imines, dimethylzinc as the methyl source with rhodium catalysis in the presence of a bidentate phosphine ligand. Reduction of the starting material was identified as side reaction with a Meerwein˗Verley˗Ponndorf type mechanism for the reduction being proposed. Addition of the imine to the reaction mixture via a syringe pump was found to minimise this by-product. The imine scope was tested with yields ranging from 34-73% and enantiomeric excesses from 75-93%. Subsequently, aryl additions were concentrated on using aryl boroxines and boronic acids to give enantioenriched diarylmethylamine products. Bis˗sulfamyl aldimines were identified as an overlooked substrate class for asymmetric aryl additions, which gave addition products that could be converted to free amines using mild basic aqueous conditions. The rhodium catalysed aryl boroxine addition using a chiral diene ligand was optimised after which a study into the reaction’s scope was carried out. Yields ranged from 37˗76% with diastereomeric ratios of 91:9˗>99:1 and enantiomeric excesses of 90˗>99%. Unfortunately, the unwanted meso-diastereoisomer could not be removed, leading to a lowering of enantiomeric excess after deprotection, nevertheless the free diarylmethylamine were isolated in yields of 31-99% and enantiomeric excesses of 82-97%. Leading on from this work, a novel class of N-sulfamyl aldimines were developed which could be deprotected under the same mild conditions, and would avoid the problem of the undesired meso-diastereoisomer. A scalable synthesis of these substrates was developed. However, aryl addition proved more problematic with imine hydrolysis being a major side reaction. Eventually a set of conditions were settled on and the scope investigated briefly. The yields were found to depend on the electronic character of the substrates and the ligand employed. Finally, a brief investigation into the iridium catalysed reductive coupling of these activated aldimines and alkynes to give allylic amines was carried out. However, useful conversions were not achieved, with imine and alkyne hydrogenation being competing reactions.